The Loners: Quarantine Series #1 - Thomas, Lex (New York : EgmontUSA, 2012)
When a virus deadly to adults infects their high school, brothers David and Will and the other students soon break into gangs that fight each other for survival and the hope of escaping their quarantine.
Keywords: Survival -- Fiction; Gangs -- Fiction; Interpersonal relations -- Fiction; Virus diseases -- Fiction; High schools -- Fiction; Schools -- Fiction; JUVENILE FICTION / Action & Adventure / Survival Stories; JUVENILE FICTION / Social Issues / Violence; JUVENILE FICTION / School & Education; Survival skills -- Fiction; Gangs -- Fiction; Interpersonal relations -- Fiction; Viruses -- Fiction; High schools -- Fiction; School stories; Science fiction